Infeksi Cacing dan Akses Jamban serta Air Bersih pada Anak Usia Sekolah Dasar - Munirah Siregar; Silvia Fitrina Nasution; Minsarnawati Minsarnawati; Mukhlidah Hanun Siregar (Tirtayasa Medical Journal, 2026)
Soil-transmitted helminthiasis (STH) remains a public health problem among school-aged children, particularly in marginalized urban settlements with inadequate sanitation. Objective: To describe the prevalence of helminth infection and household access to latrines and clean water among school-aged children in Yayasan Nanda Dian Nusantara, Ciputat Timur, South Tangerang. A descriptive cross-sectional study was conducted (October–December 2011). Consecutive sampling recruited 35 elementary-school-aged children. Data on sanitation and water were collected using questionnaires and household observations. Stool samples were examined using wet mount smear and Harada–Mori culture to identify helminth eggs/larvae. Overall, 9 of 35 children (25.7%) were positive for helminth infection. None of the participants had ever taken deworming medicine. Hookworm infection was the most common (5/9; 55.6%), followed by Fasciolopsis buski (1/9; 11.1%) and Strongyloides stercoralis (1/9; 11.1%). Two cases (22.2%) could not be identified to the species level. Most households lacked a private latrine (28/35; 80.0%) and reliable access to clean water (29/35; 82.9%). The prevalence of helminth infections was substantial and coincided with poor access to sanitation and clean water. Integrated school- and community-based strategies combining periodic deworming, hygiene promotion, and Water, Sanitation, and Hygiene (WASH) improvements are needed to reduce transmission and reinfection.